Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I need to find an expression for $n$th derivative of $f(x) = e^{x^2}$. Really need help.

share|cite|improve this question
Can you find the first few derivatives yourself? – Ben Millwood Sep 10 '12 at 17:43
Nevertheless, you'll find people much more willing to help you if you show that you've done some work yourself - besides, someone else might be able to see the pattern. – Ben Millwood Sep 10 '12 at 17:57
try taking derivative of taylor expansion of $e^{x^2}$ – Santosh Linkha Sep 10 '12 at 18:05
More generally, $$ \frac{d^n}{dx^n}e^{x^p} = \left(\sum_{k \in \mathbb{Z}}a_{n,k;p}x^{kp-n} \right) e^{x^p} $$ where the coefficients $a_{n,k;p}$ form the exponential Riordan array $A_p = [1, (1+x)^p - 1]$. This can be proved using some of the techniques from and is given as an exercise (although not in those terms) in Comtet's Advanced Combinatorics. – Peter Taylor Sep 10 '12 at 19:52
up vote 27 down vote accepted

Here is a less elementary solution.

We consider the exponential generating function

$$G(t,x) = \sum_{n=0}^{\infty} \frac{t^n}{n!} \frac{d^n}{dx^n}e^{x^2}.$$

Then we can identify this series as the McLaurin series of $e^{(x+t)^2}$ near $t = 0$. Thus we must have

$$G(t,x) = e^{(x+t)^2} = e^{x^2} e^{2xt} e^{t^2} = e^{x^2}\left( \sum_{k=0}^{\infty} \frac{(2x)^k}{k!} t^k \right)\left( \sum_{l=0}^{\infty} \frac{1}{l!} t^{2l} \right). $$

Expanding this series and comparing, we have

$$ \frac{d^n}{dx^n} e^{x^2} = \left( \sum_{j=0}^{\lfloor n/2 \rfloor} \frac{n!}{j!(n-2j)!}(2x)^{n-2j} \right) e^{x^2}. $$

Here is an example:

enter image description here

share|cite|improve this answer
I love this, particularly because my intuition was that a closed form expression using only simple operations like factorial would not be possible. – alex.jordan Sep 10 '12 at 18:46
It would be even simpler to use the Hermite polynomials for this, no? – J. M. Sep 12 '12 at 2:22
@J.M., Unfortunately I know not much about the Hermite polynomials. I have heard of these polynomials, and also know that they are closely related to the Gaussian-weighted $L^2$ space, but the important thing is that I even do not know the exact definition or a representation formula for this nice family. That's why I just made a rather elementary approach. – Sangchul Lee Sep 12 '12 at 2:37
In that case, you'll want to see the Rodrigues formula for the Hermite polynomials. Notice anything? ;) – J. M. Sep 12 '12 at 2:42
@J.M., Now it's also clear to me! We may write $$\frac{d^n}{dx^n}e^{x^2} = i^{-n}H_n(ix)e^{x^2}.$$ – Sangchul Lee Sep 12 '12 at 2:46

I'm not sure if this is what you are after, but there is a recursion that you can establish. Each derivative will be the product of a polynomial in $x$ with $e^{x^2}$. If $f^{(n)}(x)=p_n(x)e^{x^2}$, then we have $$p_0(x)=1$$ and $$p_n(x)=2x\,p_{n-1}(x)+p^\prime_{n-1}(x)$$

This recursion has the following associated infinite matrix:

$$M=\begin{bmatrix} 0 & 1 & 0 & 0 & \cdots\\ 2 & 0 & 2 & 0 & \cdots\\ 0 & 2 & 0 & 3 & \cdots\\ 0 & 0 & 2 & 0 & \cdots\\ \vdots & \vdots & \vdots & \vdots & \ddots\\ \end{bmatrix}$$

viewed as a transformation on the vector space of polynomials in $x$ with basis $\left\{1,x,x^2,x^3,\ldots\right\}$. The first column of $M^n$ gives you the $n$th derivative of $f$. If there is any hope to solve the recursion explicitly (which I'm not optimisitic for) then I'd recommend further study of this matrix. Maybe it can be diagonalized, and that would give way to a formula for $f^{(n)}$.

share|cite|improve this answer
I was hoping for some kind ofpolinomial in x with factorials , :) – Mykolas Sep 10 '12 at 17:59
Moreove, $p_n(x) = x g_n(x^2)$ for $n$ odd and $p_n(x)=h_n(x^2)$ for $n$ even. – lhf Sep 10 '12 at 18:08
Try to find more patterns with WA. – lhf Sep 10 '12 at 18:09
\prime works nice for things like $p^\prime$. – Pedro Tamaroff May 20 '13 at 23:06

Let $y=e^{x^2}$. We want to find $\frac{d^n y}{dx^n}$.

Note that $\ln y = x^2$ and so $\frac{1}{y} \frac{dy}{dx} = 2x\iff \frac{dy}{dx}=2xy$.

Differentiating again yields:


$\frac{d^3 y}{dx^3} = 2x \frac{d^2 y}{dx^2} + 4\frac{dy}{dx}$,

$\frac{d^4 y}{dx^4} = 2x \frac{d^3 y}{dx^3} + 6\frac{d^2 y}{dx^2}$.

We might guess that $\frac{d^n y}{dx^n} = 2x \frac{d^{n-1} y}{dx^{n-1}}+2(n-1) \frac{d^{n-2} y}{dx^{n-2}}$, which is easily proved by straightforward induction (we leave this as an exercise to the reader. ;) )

Let $u_k=\frac{d^k y}{dx^k}$ for easier notation. We thus have established

$u_n = 2x u_{n-1}+2(n-1)u_{n-2}$.

It is easy to find that the coefficient of $x^n y$ in $u_n$ is $2^n$, but I'm not seeing any nice way of solving the recursion at the moment.

share|cite|improve this answer
ty @Arkan Megraoui – Mykolas Jul 24 '14 at 8:18

Another approach is to write:$$f(x+y)=\sum_{n=0}^\infty \frac{f^{(n)}(x)}{n!} y^n$$

Now $f(x+y)=f(x)f(y)e^{2xy}$. So if we let $g_n(x)=f^{(n)}(x)/f(x)$ then we see that:

$$f(y)e^{2xy} = \sum_{n=0}^\infty \frac{g_n(x)}{n!}y^n$$

But $$f(y)=\sum_{k=0}^\infty \frac{1}{k!} y^{2k}$$ and $$e^{2xy} = \sum_{m=0}^\infty \frac{(2x)^m}{m!}y^m$$


$$f(y)e^{2xy} = \sum_{n=0}^\infty \frac{y^n}{n!} \sum_{m+2k=n} \frac{(2x)^m n!}{m!k!}$$

which gives us $$g_n(x)=\sum_{m+2k=n} \frac{(2x)^m n!}{m!k!}=\sum_{k=0}^{\lfloor n/2\rfloor}\frac{2^{n-2k}n!}{(n-2k)!k!}x^{n-2k}$$

And $f^{(n)}(x)=f(x)g_n(x)$.

share|cite|improve this answer
Well, I see @sos440 beat me to this answer, but since my answer is slightly organized differently, I'll leave it as is. – Thomas Andrews Sep 10 '12 at 19:27

I love to see questions like this in patterns/scheme. After the already given complete answers (especially the comment of Peter Taylor contains a very nice formal statement) here one more version, but which focuses on the visibility of the pattern in the coefficients. In Pari/GP I simply called

   (exp(x^2) )        / exp(x^2)   
   (exp(x^2) ')       / exp(x^2)   
   (exp(x^2) '' )     / exp(x^2)   
   (exp(x^2) ''' )    / exp(x^2)   

with so many apostrophes as needed for the n'th derivative. In the result

  1 + O(x^34)
  2*x + O(x^33)
  2 + 4*x^2 + O(x^32)
  12*x + 8*x^3 + O(x^31)
  12 + 48*x^2 + 16*x^4 + O(x^30)
  120*x + 160*x^3 + 32*x^5 + O(x^29)
  120 + 720*x^2 + 480*x^4 + 64*x^6 + O(x^28)
  1680*x + 3360*x^3 + 1344*x^5 + 128*x^7 + O(x^27)
  1680 + 13440*x^2 + 13440*x^4 + 3584*x^6 + 256*x^8 + O(x^26)

I find the pattern:

                                                   1      = exp(x^2)/exp(x^2)
                                                   2*x    = exp(x^2)'/exp(x^2)
                                    2* 1* 1      + 4*x^2  = exp(x^2)''/exp(x^2)
                                    2* 2* 3*x    + 8*x^3  = ...
                     3*4* 1* 1     +2* 4* 6*x^2 + 16*x^4  = ...
                     3*4* 2* 5*x   +2* 8*10*x^3 + 32*x^5  = ...
    4*5*6* 1* 1    + 3*4* 4*15*x^2 +2*16*15*x^4 + 64*x^6  = ...
    4*5*6* 2* 7*x +  3*4* 8*35*x^3 +2*32*21*x^5 +128*x^7  = ...

After that I find it obvious how this continues (formal description&proof are in the other answers above) and leave that schematic description just for the accidental later reader here.

share|cite|improve this answer

The values of the derivatives all multiplied by a factor of $e^{x^2}$ are


$2 + 4x^2$

$8x + 4x + 8x^2 = 12x + 8x^2$

$12 + 16x + 24x^2 + 16x^3 $

The if this polynomial progression is called $Q(n)$ the general pattern is:

$Q(n+1) = Q'(n) + 2xQ(n)$ where $Q(0) = 1$

share|cite|improve this answer

Related problems (I), (II), (III), (IV), (V), (6), (7). I already posted a solution on this website related to this one.

Here is the first formula, which gives only the $n$th derivative of integer order of ${\rm e}^{x^2}$

$$ {{\rm e}^{{x}^{2}}}\sum _{s=0}^{n} \left( {x}^{2\,s-n}\sum _{k=0 }^{n}{2}^{k+s} \left[\matrix{n\\k+s}\right] \left\{\matrix{k+s\\s}\right\} \right)\,, $$

where $\left[\matrix{n\\k+s}\right]$ and $\left\{\matrix{k+s\\s}\right\}$ are the Stirling numbers of the first kind and the second kind respectively.

The second formula is more general. It is a unified formula for the $n$th derivative and the $n$th anti derivative of real orders (including integer orders) of ${\rm e}^{x^2}$ in terms of the Meijer $G$-function,

$$ \left( -1 \right)^{\frac{n}{2}}{2}^{n} G^{1, 2}_{2, 3}\left(-{x}^{2}\, \Big\vert\,^{-\frac{n}{2}, -\frac{n}{2}+\frac{1}{2}}_{-\frac{n}{2}, \frac{1}{2}, 0}\right)\,.$$

Note that,

(i) if $n > 0$, then the formula gives derivatives of order $n$ ($n$ can be integer or real ).

(ii) if $ n<0 $, then the formula gives anti-derivatives of order $n$ ($n$ can be integer or real).

(iii) if $n=0$, then it gives the original function.

See references (I) and (II) for the details.

share|cite|improve this answer

The derivatives at $0$ may be found simply using the Taylor expansion: $$e^x = \sum_{k=0}^\infty {\frac{x^k}{k!}}$$ So that: $$e^{x^2} = \sum_{k=0}^\infty {\frac{x^{2k}}{k!}} = \sum_{k=0}^\infty {\frac{x^{k}}{k!}f^{(k)}(0)}$$ Leading to: $$f^{(2n)}(0) = {(2n)! \over n!} , \ f^{(2n+1)}(0) = 0$$ This means that for $f^{(n)}(x) = p_n(x) e^{x^2} = (\sum a^{(n)}_k x^k) e^{x^2}$:

$$a^{(2n)}_0 = {(2n)! \over n!}, \ \ a^{(2n + 1)}_0 = 0$$ And using alex's recursion: $$a^{(2n - 1)}_1 = {(2n)! \over n!}$$

share|cite|improve this answer
Ty nbubis, just I didn't understand this line: – Mykolas Sep 10 '12 at 19:21
$$e^{x^2} = \sum_{k=0}^\infty {\frac{x^{2k}}{k!}} = \sum_{k=0}^\infty {\frac{x^{k}}{k!}f^{(k)}(0)}$$ – Mykolas Sep 10 '12 at 19:21
i mean just the last part of it $f^{(k)}(0)$ – Mykolas Sep 10 '12 at 19:24
@Mykolas - That's just the definition of a taylor series. – nbubis Sep 10 '12 at 20:25

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.